Association between social-cognitive factors and sexual intention towards pre-marital sex activity among school-going late adolescents in Kuantan, Pahang - Abdullah, Fa’iza; A. Rahman, Nor Azlina; Muhammad, Noor Azimah; Samsudin, Suhaiza; Zainuddin, Nur Akmanidar; Draman, Samsul (2020)
The Theory of Planned-Behavior (TPB) is determined by four main domains of socialcognitive factors; attitudes, social-norms, self-efficacy and sexual intention. Pre-marital sex associated with increased risk of STDs and detrimental social implications. The study aims to explore the association between socio-cognitive factors and sexual intention (of performing sexual activities) towards premarital sex among late adolescents in Kuantan secondaryschools. This cross-sectional study was conducted in nine government secondary-schools in Kuantan district between February-Jun 2018 using a self-administered validated Youth Sexual -Intention Questionnaire (YSI-Q). A total of 466 data are collected among unmarried students aged 18-19 years old. Statistical analyses were done using IBM SPSS version 22.0. Study showed 67.4%, 68.2%, 64.4% are Malays, Females and Muslims. Simple logistic regression on socio-cognitive factors showed for every; one unit increase in permissive attitude, socialnorms and self-efficacy scores, there were 1.424, 1.303 and 1.215 times increase risk of having sexual intention, with p-value of 0.001 each and 95%CI of odds ratio (OR) 1.2681.600, 1.191-1.425 and 1.066-1.386, respectively. Multivariate logistic regression showed male, non-Malay and ever-smoker students have higher risk towards having sexual intention with a p=0.001 and OR=0.163(95%CI=0.058-0.462); OR=5.110(95%CI=1.881-13.886); OR=3.288(95%CI=1.218-8.875), respectively. For every unit increase in permissive attitude score, there was 1.236 times increase risk of having sexual intention with p=0.002 and 95% CI of OR=1.084-1.410. Otherwise parental education level, dating status and total household income were not significantly associated. The study showed the risk of having sexual intention was higher among males, non-Malay and ever-smoker students; and among those with higher permissive attitude scores. Peer education intervention program in school is essential to improve the permissive attitude in averting risk behavior that may lead to pre-marital sex activity. The study should be expanded to adolescent who are no longer in school or in suburban areas.